Ultrafine cable-like WC/W2C heterojunction nanowires covered by graphitic carbon towards highly efficient electrocatalytic hydrogen evolution. Issue 31 (27th July 2018) - Zhang, Lu-Nan; Ma, Yuan-Yuan; Lang, Zhong-Ling; Wang, Yong-Hui; Khan, Shifa Ullah; Yan, Gang; Tan, Hua-Qiao; Zang, Hong-Ying; Li, Yang-guang
Abstract : A carbon-coated ultrafine cable-like WC/W2 C heterojunction nanowire electrocatalyst exhibits remarkable HER performance in a wide pH range. Abstract : Developing highly active, durable and economical noble-metal-free electrocatalysts for the hydrogen evolution reaction (HER) plays a crucial role in the future hydrogen economy. Herein, ultrafine cable-like WC/W2 C heterojunction nanowires (NWs) covered by few-layer N-doped graphite-like carbon (labeled WC/W2 C@C NWs) have been firstly accomplished via a simple two-step pyrolysis treatment of W18 O49 NWs precursor, exhibiting tunable phase composition, excellent HER activity, fast kinetic metrics and remarkable stability along the entire pH range. With the optimized phase composition, WC/W2 C@C NWs (WC : W2 C ≈ 1 : 1.3) display the low overpotentials of 69 mV and 56 mV at the cathodic current density of 10 mA cm −2 and small Tafel slopes of 52 and 59 mV dec −1 in 0.5 M H2 SO4 and 1 M KOH, respectively. DFT calculations and experimental results demonstrate that such prominent performance towards the HER was mainly attributed to abundant interfaces between WC and W2 C phases in the cable-like heterojunction nanowires which may exert both the high HER activity of W2 C and the excellent electrochemical stability and conductivity of WC. Furthermore, the one-dimensional (1D) nanowire morphology and graphite-like carbon shells also promote the conductivity of the whole electrocatalytic material. This work presents a new route to accomplish the morphology control, composition and electronic regulation so as to boost the HER performance of tungsten-carbide-based electrocatalysts, providing new guidance for exploring efficient noble-metal-free electrocatalysts.